Analisis Skalogram: Studi Kasus Pengembangan Kopi Mamasa Berbasis Kesesuaian Lahan dan Sarana Fasilitas Penunjang di Kabupaten Mamasa : Scalogram Analysis: Case Study of Mamasa Coffee Development Based on Land Suitability and Supporting Facilities in Mamasa Regency - Chairuddin, Zulkarnain; Abdullah, Nuryahya (Jurnal Ecosolum, 2023)
To optimize Mamasa coffee production, a land use model that is appropriate to its designation is needed. The actual coffee area in Mamasa Regency reached 33,589.79 ha with a total of 20,980 farmer heads of households. This means that a large number of Mamasa people depend on Mamasa coffee. Analyze the land suitability of Mamasa coffee in relation to the regional hierarchy based on the availability of coffee supporting facilities in Mamasa Regency. Data analysis used the land suitability analysis method combined with a scalogram, to see contextually the process of intensification and development of Mamasa coffee supporting facilities. The results of this study indicate that most of the land for the business of managing Arabica and Robusta coffee plants is dominantly constrained by the physical conditions of the area where around 84.5% of the land is not suitable (N) with dominant slopes with erosion hazards (eh), root media (rc) and water availability (wa) in several open locations. In addition, the availability of coffee supporting facilities in Mamasa Regency is dominant in hierarchy 3 of 88%, while hierarchy 2 is only 9% and hierarchy 1 is 3%. This means that the facilities in Mamasa Regency in order to support coffee development related to processing facilities to marketing are still minimal. The Government of Mamasa Regency needs to pay attention to the improvement of coffee supporting facilities, especially in areas that are suitable land for Mamasa coffee, so that the intensification of coffee production in the upstream can be optimized and increased marketing in the downstream.